Study on Non-Darcian Flow in Interlayer Shear Weakness Zones in the Basalt by High-Pressure Packer Tests. (28th October 2021) - Shen, Qi; Zhou, Zhifang; Chen, Meng; Wang, Zhe; Li, Yabing
Abstract : The interlayer shear weakness zone (ISWZ) is a special structural plane with different widths and spacing in stratified rock masses, it has higher permeability compared with surrounding rocks which is a risk factor for the safety of the hydropower station project. The high-pressure packer test (HPPT) by step injection is always applied to characterize the permeability of ISWZ. However, the non-Darcian flow is easy to appear under high pressure, which makes the Darcy law model no longer applicable. In this study, two non-Darcian flow analytical methods for confined aquifer were proposed to investigate the non-Darcian flow permeability parameters. The equivalent permeability coefficients of different non-Darcian models were derived as well. The in situ tests were conducted on the ISWZs at the Baihetan hydropower station to verify the proposed methods. The results indicate that the flow is non-Darcian flow in the test section from integrity to destruction during the whole HPPT process. Izbash's law has a better fit than Forchheimer's law in this complicated test situation. The equivalent permeability coefficients after destruction are one or two orders of magnitude larger than those before. Meanwhile, it is necessary to pay attention to the increased difference of two expressions of the equivalent permeability coefficients under higher gradient ( i ) or velocity ( v ). In general, these methods can be used to evaluate the characteristic of ISWZ to analyze the impact on engineering stability.